Go fish - LePorte, George; Simeone, Lawrence (Plattsburgh, New York Direct Source Special Products, 2000)
It's a full house when the Johnson family siblings reunite for a weekend in this heart wrenching drama. There's Sammy, a diner waitress struggling to make ends meet. Her brother Richard is a powerful L.A. lawyer with an uptight, high society wife. Another brother, Alan is a poker-faced drifter with a checkered past and a wild new girlfriend, Karman. After their mother's death, they all gather at the family cabin to put aside their differences and choose who will take care of Timmy, their mentally challenged brother. Over the course of the weekend, they share stories, uncover secrets, reconcile with the past and decide their future.
Executive producer, Paul Hamilton.
George LePorte, Ara Celi, Kristen Shaw, Polly W. LePort.
Dolby digital.
In English.
Keywords: Feature films